The Effect of Situational Leadership Style and Power Distance to Employee Performance through Employee Engagement in UD. Ony Central Java Province - Fitri Rezeki; Fachrurazi Fachrurazi; Retno Purwani Setyaningrum (Universitas Dharma Wacana, 2022)
The main objective of this study was to find performance determinants of the employees of UD. This research data is sourced from the dissemination of questionnaires conducted by as many as 98 employees of trade businesses spread across ten districts and cities of Province Central Java. Following data collection, smart partial least square (PLS) software is used to evaluate the data. The analysis is started by putting the outer model to the test to see how the indicator and the variables it represents relate to one another. The study concluded that the power distance had no impact on employee performance and that situational leadership style has both direct and indirect effects on employee engagement, but the energy space can be increased by implementing employee engagement. Employee engagement positively influences employee performance as a mediation between situational leadership styles and power distances.